PHARMACOGNOSTICAL ASPECTS OF GLYCYRRHIZA GLABRA - Vashist, Hemraj; Sharma, Diksha (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective-Pharmacognostical evaluations like thin layer chromatography, ash value and extractive values , Hydrodistillation, powder microscopy, extraction of ammonium and calcium glycyrrhizinate was performed for licorice powder. Method- Dried powder of licorice root was extracted with ethanol by soxhlation. Ash values, extractive values and ammonium glycyrrhizinate were obtained by standard procedures. Results-Total ash value was obtained 9.33percent while acid insoluble and water soluble ash was recorded as 2.1 whereas water soluble extractive and alcohol soluble extractive value was calculated as 19.6percent w/v and 9percent w/v. 3.5percent ammonium glycyrrhizinate from 20g powder of licorice and 4percent of calcium glycyrrhizinate was obtained from the same amount. The preliminary phytochemical screening as performed in the results saponins, flavonoids, carbohydrates and phytosterols were found to be present. Conclusion-The Preliminary phytochemical, Pharmacognostical study, ammonium glycyrrhizinate and calcium glycyrrhizinate obtained can be used for evaluation of these aspects on licorice. KEY WORDS- Pharmacognostical evaluation, ammonium and calcium glycyrrhyzinate, phytochemical screening.